POTENTIAL USE OF THERMAL CAMERA COUPLED IN UAV FOR CULTURE MONITORING - Viana, L. A.; Zambolim, L.; Sousa, T. V.; Tomaz, D. C. (Revista Brasileira de Engenharia de Biossistemas, 2018)
The highest productivity of the crop is achieved under ideal growing conditions. In the search of the ideal environment, it is necessary to constantly manage and check the cultivated area, considering the possibility of pest and disease attack, as well as stress due to lack of water and nutrients. Constant monitoring, if done manually, is extremely costly and time-consuming, as well as obtaining information that is often related to an existing problem. Studies have shown that using sensor-coupled UAVs is a way to get information and results faster than traditional agricultural management and monitoring systems. Therefore, the main purpose of this review is the use of a thermal camera coupled to UAV for monitoring agricultural culture. The studies have demonstrated the great applicability of the use of thermal cameras coupled to UAV in agriculture, since it makes it possible to evaluate from water stress to fruit damages, besides the fact that the use of UAV allows to obtain information of large areas in a space of time smaller than monitoring.